Developing Problem Based Learning through Lesson Study - Muh. Syahriridani; Herawati Susilo; Ibrohim Ibrohim (Journal of Learning Improvement and Lesson Study, 2021)
Critical thinking skills are important to be empowered in the 21st century. Critical thinking skills are the ability to collect and evaluate information to draw the right conclusions. Educators need Lesson Study (LS) activities to empower students' critical thinking skills taught by Problem-based Learning (PBL). This research was conducted on 27 third-semester students at the State University of Malang in 2021 with the aim of improving students' critical thinking skills in learning plant physiology using PBL. Improvement of the learning process is carried out with LS activities. The LS implementation phase consists of plan, do and see. Lesson Study findings obtained focus on the duration of learning, controlling student interaction in study groups, contextual problems, and selecting essential learning topics. The results of the N-Gain test in the first cycle obtained a low category score of 0.14, while in the second cycle a medium category score of 0.38 was obtained. Students' critical thinking skills are empowered through drawing conclusions from data collection to solve contextual problems.